O PARANÁ NA HISTÓRIA DA MINERAÇÃO NO BRASIL DO SÉCULO XVII - Liccardo, Antonio; Sobanski II, Arnoldo; Chodur, Nelson Luiz (Boletim Paranaense de Geociências, 2004)
Enquanto na América Espanhola os conquistadores já encontraram ouro quando chegaram, no Brasil os minérios não foram encontrados imediatamente. Os primeiros registros, em torno de 1570, apontam a região de Paranaguá, Guaraqueçaba e Cananéia, na capitania de São Vicente, como as primeiras minas cartografadas no novo território português. Até a descoberta dos garimpos de Vila Rica em Minas Gerais, em torno de 1680, a produção de ouro, que nunca chegou a ser grande, foi totalmente concentrada na Capitania de São Vicente, no território que hoje é o Paraná. Muitas vilas e cidades devem sua fundação aos eventos de mineração dessa época. Com o início do ciclo do ouro em Minas Gerais, uma forte migração aconteceu, deslocando grandes contingentes da população e relegando a região do Paraná ao abandono. Apesar das graves conseqüências sociais e econômicas dessa mudança, é possível traçar a relevância da atividade mineradora para o Paraná durante o século XVII. A presença dos garimpeiros como catalisadores de povoamento e domínio territorial é ressaltada. Além disso, sua capacidade de prospecção de minérios abriu caminho para futuras minerações sistemáticas. A experiência de aprendizagem de quase um século fez do Paraná uma espécie de protótipo para que se desenvolvesse a tecnologia necessária a se aplicar em outras regiões. PARANÁS MEANING IN THE XVII TH CENTURY BRAZILIAN MINING HISTORY Abstract Differently from Hispanic America, where conquerors found gold as they arrived, in Brazil the first signs of alluvial occurrences only appeared in Paranaguá, Guaraqueçaba and Cananéia, in the Captaincy of São Vicente in the 1570s. Until new placers settled in Vila Rica, Minas Gerais in 1680, the reduced gold production in the Portuguese America was restricted to the territory that now corresponds to the Sate of Paraná, where a number of villages and towns spread around mining nuclei. By the beginning of the 18th Century, the migration flow of adventurers and prospectors had already shifted to the hinterlands of Minas Gerais and Goiás, where production was more intense. The former 17th Century represented a cycle of prosperity in Paraná, and gold exploitation was exclusively alluvial. The main nuclei of pioneers, at first Paranaguá, Guaraqueçaba, and later Morretes, Porto de Cima and São João da Graciosa, seem to have been settled by hunters of slaves in their dreams of fast enrichment. Other nuclei were present westward over Serra do Mar Range, namely São José dos Pinhais, Curitiba, Ferraria, Bateias and Ouro Fino. Exploitation was in almost all cases related to secondary deposits. It was in Bateias and Ferraria that exploitation from outcropping quartz veins began. There, mining works such as reject piles underwent tailing production much later in the 20th Century. Placering seems to have never been totally abandoned, as occasional miners are still found in Guaraqueçaba and in the surroundings of Paranaguá. In spite of the discontinuing shock, the relevance of that period cannot be minimised, for the search for metals and enrichment brought about the progress seed to the mining areas as the presence of miners catalysed land occupation. In some cases, indicators left by the first prospectors were later incorporated into the systematic work of mining companies. Of no lesser importance is the fact that the experience gained by pioneers was important for the discovery and exploitation of new resources in Minas Gerais and Goiás. It took them a century of experience to develop the prospection technology necessary.